Meeting the food security challenge for nine billion people in 2050: What impact on forests? - Bahar, N.H.A.; Lo, M.; Sanjaya, M.; Vianen, J. van; Alexander, P.; Ickowitz, A.; Sunderland, T.C.H. (Elsevier, 2020)
• Majority forecasts for feeding the future global population predict an increase in a croplands at the expense of forests and pastures. • A third of the forecasts shows that it is feasible to halt further agricultural expansion and mitigate climate change. • Policy that provides economic incentives for carbon stock conservation and enhancement is the only effective option to reverse the trend of forest loss.